Materialism and Compulsive Buying: The Mediating Roles of Self-Control and Anxiety - Jain, Ankita; Srivastava, Dr.Sandeep; Shukla, Dr. Abhishek (South Eastern European Journal of Public Health, 2024)
Compulsive buying behavior (CBB) is a maladaptive consumption pattern characterized by excessive and uncontrolled buying that causes significant psychological, social, and financial consequences. This study investigates the roles of materialism, self-control, and anxiety in predicting compulsive buying behavior (CBB) through a serial mediation model. Data was collected from 639 participants using validated scales via a snowball approach and convenience sampling approaches. The results demonstrate that materialism exerts both direct and indirect effects on CBB. Materialism has a significant positive direct effect on CBB, suggesting that individuals with higher materialistic values are more prone to compulsive buying tendencies. Furthermore, materialism negatively impacts self-control and positively influences anxiety, which in turn contribute to increased CBB through significant indirect pathways. The model reveals that lower self-control and higher anxiety levels are directly associated with greater CBB. The findings highlight the complex interplay among these variables and the multiple pathways through which materialism can influence CBB, providing insights into the underlying mechanisms driving this phenomenon. The study has important theoretical implications for understanding CBB and practical implications for developing targeted interventions and prevention strategies that address materialistic values, enhance self-control, and manage anxiety. By integrating these factors within a unified framework, this research contributes to a more comprehensive understanding of compulsive buying behavior and its antecedents.